Ética no cuidado em saúde e na formação universitária na perspectiva da educação popular - Batista, Patrícia Serpa de Souza (2012)
The popular health education includes actions involving the dimensions of the dialogue, the problematization, the respect and the appreciation of popular knowledge. It also operates in a policy perspective directed to the search for implementation of changes in reality, of social justice, bringing, thus, a specific conception of ethics for the health and for the university education. This study aims to analyze ethics in educational and care actions guided by the popular health education, based on the experience of students from the university extension project, Popular Education and Attention to the Family‟s Health (PEAFH), and analyze the ethical training of university students from the perspective of popular health education, based on the experience of that project. We assume that ethics, guided by popular health education, involves a dialogical and problematizing conception, which transposes the perspective of compliance of codes of ethics, usually valued in teaching health, and that includes the concern of students with social justice. This is a qualitative research conducted in a dialectical perspective. The investigation scenario was the Maria de Nazaré Community, located in the city of João Pessoa PB. Participated in the survey five teachers and forty students of PEAFH, three ex students from the extension, three community leaders, three health community agents and six community residents. Data collection took place during the year of 2010, by use of participant observation techniques, focal group and interview. Were also used as empirical data sources, seven statements written by six students and an ex student from the extension, to compose a book on the PEAFH. The empirical material was subjected to thematic content analysis, originating ten thematic categories, among which stand out: the initial contact of the student with the community and the gradual process of formation of bond with the families; approximation of the student a complementizer ethics perspective of care within the family; and the involvement with political struggles of the community; the learning to live with tensions and conflicts and ethical living between teacher and student in the development of the Project. This data analysis gave rise to reflections on ethics in educational and care actions of students guided by popular health education and about the guiding ethics of pedagogical training of students in the perspective of popular health education. This study enabled the confirmation that ethics in the perspective of popular health education in the care of health and in formation mainly involves the methodology of dialogue and problematization of reality and the concern with social justice and also shows an affective bond as structuring of ethical actions. Thus, the study contributes to building a differentiated ethics in the health field, guided by popular education.